Quality of maternal and newborn healthcare services in two public hospitals of Bangladesh: identifying gaps and provisions for improvement - Taposh Kumar Biswas; Hasnat Sujon; M. Hafizur Rahman; Henry B. Perry; Mahbub Elahi Chowdhury (BMC Pregnancy and Childbirth, 2019)
Abstract Background Healthcare service delivery systems need to ensure standard quality of care (QoC) for achieving expected health outcomes. Although Bangladesh has a good healthcare service delivery system, there are major concerns about the quality of maternal and newborn health (MNH) care services, which is imperative for achievements in health. The study aimed to measure the QoC for different MNH services in two selected public health facilities of Bangladesh. This study also documented the specific areas of each care which needs intervention. Methods The study was conducted in two district-level public health facilities—a district hospital (DH) and a mother and child welfare centre (MCWC). A total of 228 cases of MNH services were observed by using contextualized checklist ‘Standards-based Management and Recognition (S-BMR)’ for 8 selected MNH care services. For scoring, performed activities were calculated as percentages of the total recommended activities and categorized as high (> 80%), moderate (50 to 80%), and low (< 50%). Results Overall QoC scores were moderate for each DH (54.8%), and MCWC (56.1%). In DH, the QoC score was high for blood transfusion (80.3%); moderate for maternal complications management (77.0%), caesarean section (CS) (65.6%), infection prevention (64.3%), sick newborn care (54.1%), and normal vaginal delivery (NVD) (52.6%); and low for antenatal care (ANC) (25.6%) and postnatal care (PNC) (19.0%). In MCWC, the QoC scores were high for infection prevention (83.0%); moderate for CS (76.5%) and NVD (59.8%); and low for ANC (36.9%) and PNC (24.5%). Conclusions In the study facilities, the QoC for MNH services is found to be unsatisfactory, particularly for ANC and PNC. Urgent initiative needs to be taken by introducing contextualized quality monitoring tools at health facilities, along with training of the care providers and introducing a quality monitoring system.